Pengaruh Harga, Ulasan Produk, Kemudahan Transaksi, Kualitas Informasi dan Kepercayaan Terhadap Keputusan Pembelian Produk Kecantikan Secara Online Pada Marketplace Shopee - Nunik Restuti; Marlina Kurnia (Universitas Muhammadiyah Magelang, 2022)
The purpose of this study was to examine the effect of price, product reviews, ease of transaction, quality of information, and trust in online purchasing decisions for beauty products on the Shopee marketplace. The sample collection technique is the Accidental Sampling technique with a total sample of 100 respondents, namely consumers who have purchased beauty products online on the Shopee marketplace. The analytical tool used is multiple linear regression using the SPSS 25 program. The research shows that price, information quality, and trust variables have no effect on purchasing decisions for online beauty products on the Shopee marketplace, while product reviews and transaction convenience variables have a positive and significant effect on the decision to purchase beauty products online on the Shopee marketplace.